SHREC'16 track: Shape retrieval of low-cost RGB-D captures - Pascoal, P. B.; Proença, P.; Gaspar, F.; Dias, M. S.; Ferreira, A.; Tatsuma, A.; Aono, M.; Logoglu, K. B.; Kalkan, S.; Temizel, A.; Li, B.; Johan, H.; et al. (Eurographics 2016 Workshop on 3D Object Retrieval, EG 3DOR 2016, 2016)
RGB-D cameras allow to capture digital representations of objects in an easy and inexpensive way. Such technology enables ordinary users to capture everyday object into digital 3D representations. In this context, we present a track for the Shape Retrieval Contest, which focus on objects digitized using the latest version of Microsoft Kinect, namely, Kinect One. The proposed, track encompasses a dataset of two hundred objects and respective classification.